Effect Of Self-Efficacy: How Athletes With Disabilities In Achieve Achievements? - Latuheru, Ricardo Valentino; Arfanda, Poppy Elisano; Aprilo, Ians (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Self-efficacy is believed to be related to the ability to organize, perform tasks in achieving goals, produce and implement actions to achieve certain skills. This study aims to analyze the level of self-efficacy in athletes with disabilities in South Sulawesi. The study was conducted on 10 athletes with disabilities in South Sulawesi with the criteria for physically disabled and deaf. The data collection technique used a test instrument that adapted from The General Self-Efficacy Scale created by Aristi Born, Ralf Schwarzer & Matthias Jerusalem in 1995, with 10 questions and answers consisting of 4 scales. This questionnaire has been standardized in 32 languages and was adapted in this study in an Indonesian version. Data collection using a google form which is specifically intended for athletes with disabilities in South Sulawesi. The results of all respondents with an average of 75%, and are in the high category and they can overcome any problems that arise both during practice and during matches. The conclusion in this study is that the high self-efficacy of disabled athletes affects many things related to individual skills and abilities as athletes.